Awareness of breast cancer and barriers to breast screening uptake in Bangladesh: A population based survey. (February 2016) - Islam, Rakibul M.; Bell, Robin J.; Billah, Baki; Hossain, Mohammad B.; Davis, Susan R.
Highlights: Even though the awareness of breast cancer (BCa) is high in women at midlife in Bangladesh, screening uptake is very low. Lack of understanding of the need for assessment of women free of breast symptoms is the key obstacle to screening uptake in Bangladesh, not cultural and religious barriers. Health education programs, especially those promoting assessment of asymptomatic women, have the potential to result in down-staging of the disease. Abstract: Objectives: To investigate the awareness of breast cancer (BCa) and BCa screening amongst women at midlife in Bangladesh. Methods: A nationally representative cross-sectional survey of women aged 30–59 years was conducted in 7 districts of the 7 divisions in Bangladesh, using a multistage cluster sampling technique. The factors associated with the awareness of BCa and breast assessment of asymptomatic women were investigated separately, using multivariable logistic regression. Results: Of the 1590 participants, mean age 42.3 (±8.0) years, 81.9% had ever heard of BCa and 64.2% of any methods of BCa screening, respectively. Awareness of BCa was associated with being aged 40–49 years (adjusted OR 2.04, 95% CI 1.46–2.84), aged 49–59 years (1.96, 1.32–2.91), being overweight (1.46, 1.07–2.01) and obesity (1.62, 1.01–2.62), while inversely associated with rural dwelling (0.37, 0.22–0.61), primary education (0.44, 0.27–0.70), having no education (0.23, 0.14–0.36) and parity (0.62, 0.44–0.87). Of the 750 women who were aware of clinical breast examination (CBE) or mammography, reasons provided for not undergoing screening included that they had no symptoms (92%) and that they did not know screening was needed (40%). 8% of women reported CBE. Women with no education were less likely to have undergone CBE (0.38, 0.14 1.04; p  = 0.059). Conclusion: Lack of understanding of the assessment of asymptomatic women is the key obstacle to BCa screening uptake in Bangladesh. Health education programs, especially BCa awareness programs, have the potential to increase BCa awareness and down-staging of the disease.